Flourishing Remaja dari Keluarga Tidak Mampu: Sebuah Studi Kasus Mengenai Pengalaman Siswa Jalur Afirmasi di Sekolah Negeri Favorit - Putri Arifin; Tengku Andinny Indira; Anastasia Navydia Suwarno; Syafira Putri Giriansyah; Alisa Dzihni Al Fatihah; Rahmat Agung Hidayat; Wiwin Hendriani (INSAN Jurnal Psikologi dan Kesehatan Mental, 2026)
This study aims to explore the dimensions of flourishing based on PERMA and the external determinants of flourishing among students of the affirmation program from low-income families who attend prestigious public schools. The study employed a qualitative approach using instrumental case studies of three female students in the affirmation program at a prestigious public school. Data collection involved semi-structured interviews, and the data were analyzed using theory-driven thematic analysis. The analysis focused on the PERMA dimensions and external factors supporting flourishing. The results indicate that all participants demonstrated all five PERMA dimensions through experiences of positive emotion, engagement, relationships, meaning, and accomplishment. Additionally, flourishing was supported by external factors such as family support, peer support, teacher support, and institutional support, with peer support being the most prominent source of support. These findings suggest that external factors help shaping flourishing.